DINAMIKA POLITIK DAN STRATEGI PEMENANGAN PARTAI KEBANGKITAN BANGSA DI BENER MERIAH - Mulyadi, Mulyadi; Damayanti, Rosalina; Abdullah, Taufik; Nazarni, Nazarni; Rusydi, Rusydi (FISIP Universitas Malikussaleh, 2024)
This study examines how the political dynamics and winning strategy of the Partai Kebangkitan Bangsa (PKB) in Bener Meriah District in the 2019 legislative elections. The purpose of this study is (1) to find out the changes and developments in the political situation before and during the 2019 legislative elections in Bener Meriah District; (2) to find out the approach used by PKB in winning the legislative elections in Bener Meriah District. (3) To understand the political factors that influenced PKB's victory in the 2019 legislative elections in Bener Meriah District. This research uses a descriptive qualitative method with data collection techniques through observation, interviews and documentation. The results showed that PKB's victory in the 2019 Bener Meriah DPRK was influenced by several key factors, including first, a significant change in the political map in Bener Meriah District, including a shift in support from one party to another. Second, PKB was able to co-opt dominant local political issues and effective fundraising so that these issues influenced voter preferences. Third, PKB is able to mobilize the masses with a more personal and community-centric approach. Meanwhile, PKB's winning strategy took several tactical steps including; (1) PKB utilizes cultural and religious approaches; (2) Personal approach through local figures, dayah networks and local scholars; (3) Strengthening structures and regeneration; (4) Coalitions and strategic alliances with groups.